Pengembangan Modul Pembelajaran Berbasis Masalah Menggunakan Nearpod untuk Meningkatkan Hasil Belajar Bahasa Indonesia di Sekolah Dasar - Rochati, Uci; Suriswo, Suriswo; Nugraha, Rahmad Agung (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to develop a teaching module based on Problem Based Learning (PBL) integrated with Nearpod technology for Indonesian language learning on the topic "Bartering and Paying" in Grade IV at SDN 03 Tanahbaya, Pemalang. The background of the study is the low student learning outcomes and lack of active engagement in conventional learning methods. The study adopts a Research and Development (R&D) method using a simplified ADDIE model, limited to three stages Analysis, Design, and Development. The results show that the developed teaching module received a "highly feasible" rating from subject matter and media experts. The module was also considered practical based on positive responses from teachers and students. The module's effectiveness was tested through pre-test and post-test results, showing a significant improvement in student learning outcomes after using the module. Furthermore, the integration of Nearpod provided a more interactive and engaging learning experience for students. In conclusion, the PBL-based teaching module integrated with Nearpod effectively improved student learning outcomes and supported the implementation of the Independent Curriculum. This study recommends the use of similar modules in Indonesian language learning and other subjects to encourage active and meaningful learning in elementary schools.